High Performance Ultra-Low Energy RRAM with Good Retention and Endurance - Cheng, C. H.; Tsai, C. Y.; Chin, Albert; Yeh, F. S. (My University, 2010)
High performance novel RRAM of 0.3 mu W set power (0.1 mu A at 3 V), 0.6 nW reset power (-0.3 nA at -1.8 V), fast 20 ns switching time, ultra-low 6 fJ switching energy, large 7x10(2) resistance window for 10(4) sec retention at 125 degrees C, and 10(6) cycling endurance were measured simultaneously. This is the first time that the switching energy of new non-volatile memory is close to existing Flash Memory.